Synthesis and Characterization of Rare‐Earth Orthoferrite LnFeO3 Nanoparticles for Bioimaging. Issue 31 (8th August 2018) - Pinho, Sonia L. C.; Amaral, João S.; Wattiaux, Alain; Duttine, Mathieu; Delville, Marie‐Hélène; Geraldes, Carlos F. G. C.
Abstract : A combination of sol–gel synthesis and thermal decomposition was developed for preparing nanosized, perovskite‐type LnFeO3 (Ln = Eu, Gd, Tb) powders. Perovskite‐type powders with crystalline particles of 100 nm average size, as determined by transmission electron microscopy (TEM), could be obtained after a thermal treatment at 800 °C. The perovskite nanoparticles (NPs) were further characterized by X‐ray powder diffraction and Mössbauer spectroscopy. These were in agreement with the pure perovskite LnFeO3 structure with the expected Zeeman sextet corresponding to a magnetically ordered phase. Magnetization measurements [ M ( H )] at 5 K and 300 K showed a behavior that is dominated by antiferromagnetic interactions and weak ferromagnetism in EuFeO3, while for Ln = Gd, Tb, they were dominated by the low ordering temperature Ln magnetic sublattice. The colloidal aqueous NPs suspensions exhibited no significant leaching of free Ln 3+ ions. Their relaxivities define them as potential T 2 MRI contrast agents for further biomedical applications. The NPs showed fast uptake and no cytotoxicity at concentrations below 62.5 µg/mL with respect to Hela cells. Abstract : Rare‐earth orthoferrite nanoparticles (LnFeO3 ), synthesized by sol–gel synthesis and thermal decomposition, act as potential MRI contrast agents.